Hydrophobic modified coal powder and preparation method thereof
By mixing surfactant and nano-silica with coal powder, hydrophobic modified coal powder is formed, which solves the problem of high cost of low-order coal moisture reabsorption and non-evaporation technology, and achieves long-term drying and combustion efficiency of coal powder.
Patent Information
- Application Number
- CN202211202065.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-09-29
AI Technical Summary
In the prior art, low-order coals are prone to moisture resorption in the air after drying, and the temperature and pressure required for non-evaporation technology treatment are high, equipment costs are high, and industrial wastewater is difficult to recycle.
By mixing surfactant and nanosilicon dioxide with coal powder, hydrophobic modified coal powder is formed, and the pore structure of the coal powder is shielded and sealed by surfactant and nanosilicon dioxide to inhibit its water absorption performance.
It effectively reduces the moisture reabsorption rate of coal powder, ensures long-term drying, improves the combustion calorific value and utilization efficiency of coal powder, and reduces the preparation cost and equipment requirements.
Smart Images

Figure CN115404113B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of low-rank coal quality improvement and utilization, and specifically relates to a hydrophobic modified coal powder and a preparation method thereof. Background Art
[0002] my country's resource endowment determines that coal will remain my country's main energy source for a long time in the future. Low-rank coal, mainly lignite, is my country's main coal resource, accounting for more than half of the total reserves, and is the main fuel for my country's thermal power plants. Low-rank coal has a low degree of metamorphism, high oxygen content, and strong water absorption capacity. In the eastern, southern and coastal areas of my country, the air humidity is high all year round, and the moisture content in low-rank coal exceeds 20%, even reaching 40%. The high moisture content in coal seriously affects the combustion calorific value and utilization efficiency.
[0003] In industrial practice, coal evaporation drying technology is often used, including steam or flue gas drum drying, fluidized bed drying, microwave drying and solar drying to evaporate the moisture in low-rank coal, but the coal sample will reabsorb moisture in the air after drying. Non-evaporation technology, such as hydrothermal treatment HTD, solvent dehydration and mechanical hot pressure dehydration MTE, can well solve the problem of moisture reabsorption in dry coal samples, but it requires higher temperature and pressure, increases equipment cost, and the industrial wastewater generated in its production process is difficult to recycle. Summary of the invention
[0004] The purpose of the present application is to provide a hydrophobic modified coal powder and a preparation method thereof, so as to solve the technical problems that the coal samples treated by evaporation drying technology in the prior art will reabsorb moisture in the air, the temperature and pressure required for treating the coal samples by non-evaporation technology are high, the equipment cost is large, and the industrial wastewater generated in the production process is difficult to recycle.
[0005] In order to achieve the above purpose, a technical solution adopted in this application is:
[0006] A method for preparing hydrophobic modified coal powder is provided, comprising:
[0007] Mixing a surfactant and nano-silicon dioxide in water to obtain a first mixed solution;
[0008] adding coal powder to the first mixed liquid and mixing to obtain a second mixed liquid;
[0009] The second mixed liquid is filtered, washed, and dried to obtain hydrophobic modified coal powder.
[0010] In one or more embodiments, the surfactant is a gemini surfactant.
[0011] In one or more embodiments, the surfactant is a cationic gemini surfactant, and the surfactant molecular structure is
[0012]
[0013] Wherein, m represents the number of carbon atoms in the straight-chain alkyl group, and m is 8, 10, 12, 14, 16 or 18; j represents the number of carbon atoms in the bridge-chain branched alkyl group, and j is 2, 4 or 6; and X is a bromide ion or a chloride ion.
[0014] In one or more embodiments, in the step of mixing the surfactant and nano-silica in water, the mass ratio of the surfactant, nano-silica and water is (0.075-0.60): (0.5-1.0): (1000-1500).
[0015] In one or more embodiments, the particle size of the nano-silicon dioxide is less than 100 nm. In one or more embodiments, the step of mixing the surfactant and the nano-silicon dioxide in water is specifically performed by ultrasonication for 5 to 40 minutes.
[0016] In one or more embodiments, the coal powder is dry coal powder, and the particle size of the coal powder is less than 0.5 mm.
[0017] In one or more embodiments, the step of adding coal powder to the first mixed liquid and mixing the mixture is specifically performed by ultrasonication for 20 to 60 minutes.
[0018] In one or more embodiments, in the step of adding coal powder to the first mixed liquid for mixing, the mass ratio of the coal powder to the first mixed liquid is (0.50-2.0): (500-1000).
[0019] In order to achieve the above purpose, another technical solution adopted by this application is:
[0020] Provided is a hydrophobic modified coal powder prepared by the preparation method described in any one of the above embodiments.
[0021] Different from the prior art, the beneficial effects of this application are:
[0022] The hydrophilic sites, some gaps and pore structures of the hydrophobically modified coal powder of the present application are shielded and closed by surfactants and nano-silicon dioxide, thereby effectively inhibiting its water absorption performance and avoiding the phenomenon of water reabsorption. Compared with the untreated coal powder, the reabsorption rate of water is reduced by 49%, ensuring long-term drying and effectively improving the combustion calorific value and utilization efficiency of the coal powder.
[0023] The preparation method of the hydrophobically modified coal powder of the present application has simple conditions, is convenient and quick to operate, has low cost, and does not require changes to existing equipment. At the same time, it can effectively inhibit the reabsorption of water in the coal powder and effectively ensure the long-term drying of the coal powder, thereby improving the combustion calorific value and utilization efficiency of the coal powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic flow chart of an implementation method of a method for preparing hydrophobically modified coal powder of the present application. DETAILED DESCRIPTION
[0025] The present application will be described in detail below in conjunction with the various embodiments shown in the accompanying drawings. However, these embodiments do not limit the present application, and any structural, methodological, or functional changes made by a person of ordinary skill in the art based on these embodiments are all included in the protection scope of the present application.
[0026] Low-rank coal, mainly lignite, is the main coal resource in my country, accounting for more than half of the total reserves and is the main fuel for my country's thermal power plants. Due to its strong water absorption capacity, lignite has a high moisture content, which seriously affects its combustion calorific value and utilization efficiency.
[0027] In the prior art, in order to solve the problem of water absorption of lignite, evaporation technology and non-evaporation technology are mainly used to treat lignite. Among them, evaporation technology mainly uses high-temperature heating and drying methods such as drum drying and fluidized bed drying. After heating and drying, the coal sample will also reabsorb water in the air, making it difficult to ensure the dryness of the coal sample for a long time. Although non-evaporation technology can solve the problem of water reabsorption of dry coal samples, the cost of treatment is high, and a large amount of industrial wastewater that is difficult to recycle will be generated during the treatment process, which is not conducive to sustainable development.
[0028] In order to solve the problem of moisture reabsorption of low-rank coal, the applicant has developed a method for preparing hydrophobic modified coal powder. The method has simple preparation conditions, convenient and quick operation, low cost, and does not require changes to existing equipment. At the same time, it can effectively inhibit the moisture reabsorption of coal powder and effectively ensure the long-term drying of coal powder, thereby improving the combustion calorific value and utilization efficiency of coal powder.
[0029] Specifically, see Figure 1 , Figure 1 It is a schematic flow chart of an implementation method of a method for preparing hydrophobically modified coal powder of the present application.
[0030] The preparation method comprises:
[0031] S100, mixing a surfactant and nano-silicon dioxide in water to obtain a first mixed solution.
[0032] Firstly, a surfactant is used to adsorb nano-silica, so that the surface sites of nano-silica change from negative charge to positive charge, making it easy to adsorb in the gaps and pore structures of low-rank coal with negative charge on the surface.
[0033] In one application scenario, the surfactant is a gemini surfactant. Compared with single-chain surfactants, gemini surfactants have one more hydrophobic group and hydrophilic group. At the same time, the bridge bond connecting group in the molecular structure of the gemini surfactant has the effect of weakening the electrostatic repulsion between the hydrophilic head groups of the surfactant, which can improve the adsorption density of the surfactant on the coal powder surface.
[0034] Specifically, the surfactant may be a cationic gemini surfactant having a molecular structure of:
[0035]
[0036] It can be abbreviated as mjm(X), wherein m represents the number of carbon atoms in a straight-chain alkyl group, m is 8, 10, 12, 14, 16 or 18, represents the number of carbon atoms in a bridged branched alkyl group, j is 2, 4 or 6, and X is a bromide ion or a chloride ion.
[0037] In one application scenario, the particle size of nano-silicon dioxide is less than 100 nm, thereby ensuring the dispersion effect of nano-silicon dioxide in the gaps and pore structures of coal powder.
[0038] In one application scenario, the mass ratio of surfactant, nano-silica and water is (0.075-0.60):(0.5-1.0):(1000-1500).
[0039] In one application scenario, the surfactant and nano-silica can be mixed in water by ultrasonic treatment for 5 to 40 minutes, and the ultrasonic treatment ensures the uniform dispersion of the surfactant and nano-silica.
[0040] S200, adding coal powder to the first mixed liquid and mixing to obtain a second mixed liquid.
[0041] The surfactant and charged nano-silica particles jointly adsorb the negatively charged coal powder particles on the surface, shielding the hydrophilic points on the surface of the low-rank coal and blocking and filling the gaps and pore structures within a certain range, reducing the water absorption capacity and moisture storage space of the low-rank coal, thereby achieving the purpose of inhibiting the reabsorption of moisture.
[0042] In one application scenario, when the surfactant is a gemini surfactant, since the bridge bond of the gemini surfactant can effectively inhibit the electrostatic repulsion between the hydrophilic head groups of the surfactant, it can further improve the adsorption density of the surfactant molecules on the coal powder surface and further reduce the water absorption capacity of the coal powder.
[0043] In one application scenario, the method of adding coal powder to the first mixed liquid for mixing can be ultrasonic treatment for 20 to 60 minutes. The ultrasonic treatment method can effectively destroy the weak interaction between the surfactant and the hydrophobic surface of the coal, such as the hydrophobic bonding, while retaining the strong electrostatic interaction between the surfactant and the hydrophilic surface of the coal, thereby eliminating invalid adsorption, reducing the adsorption amount, and improving the hydrophobic effect.
[0044] In an application scenario, in order to ensure the dryness of the processed coal powder and prevent moisture from being trapped in the gaps and pore structures of the coal powder, the coal powder is dry coal powder, and the particle size of the coal powder can be less than 0.5 mm.
[0045] In one application scenario, the mass ratio of coal powder to the first mixed liquid may be (0.50-2.0):(500-1000).
[0046] S300, filtering, washing and drying the second mixed liquid to obtain hydrophobic modified coal powder.
[0047] The second mixed liquid is filtered to obtain collected filter material, which is rinsed with water to remove residual unabsorbed surfactant and nano-silicon dioxide, and then dried to remove moisture on the surface of the coal powder to obtain hydrophobically modified coal powder.
[0048] In one application scenario, the drying can be carried out in an oven at 105° C. for 5-24 hours. In other application scenarios, other drying methods can also be used to achieve the effect of this embodiment.
[0049] The present application also provides a hydrophobic modified coal powder prepared by the above-mentioned preparation method, the gaps and pore structure of the hydrophobic modified coal powder are sealed by surfactants and nano-silicon dioxide, thereby effectively inhibiting its water absorption performance, ensuring long-term drying, and effectively improving the combustion calorific value and utilization efficiency of the coal powder.
[0050] The present application is further described below in conjunction with specific examples. The experimental materials used in the following examples were purchased from conventional reagent companies.
[0051] Embodiment 1:
[0052] A hydrophobic modified coal powder is prepared by the following steps:
[0053] 1) Dissolve 75 mg of a Gemini surfactant in 1000 parts by weight of water to obtain a surfactant solution, wherein the molecular structure of the Gemini surfactant is 8-6-8 (Br), then add 0.5 g of nano-silica, and ultrasonicate for 5 minutes to obtain a surfactant-nano-silica mixed solution.
[0054] 2) 50 mg of coal powder was added to 500 g of the surfactant-nano-silicon dioxide mixed solution obtained in step (1), and ultrasonic treatment was continued for 20 minutes.
[0055] 3) The mixed solution after ultrasonic adsorption is filtered and then washed with water. The obtained filter cake is placed in an oven at 105° C. and dried for 5 hours to obtain modified coal powder.
[0056] Embodiment 2:
[0057] A hydrophobic modified coal powder is prepared by the following steps:
[0058] 1) 600 mg of Gemini surfactant was dissolved in 1500 g of water to obtain a surfactant solution, wherein the molecular structure of the Gemini surfactant was 18-4-8 (Cl), and then 1.0 g of nano-silicon dioxide was added, and ultrasonicated for 40 minutes to obtain a surfactant-nano-silicon dioxide mixed solution.
[0059] 2) Add 2.0 g of coal powder to 1000 g of the surfactant-nano-silicon dioxide mixed solution obtained in step (1), and continue ultrasonication for 60 minutes.
[0060] 3) The mixed solution after ultrasonic adsorption is filtered and then washed with water. The obtained filter cake is placed in an oven at 105° C. and dried for 24 hours to obtain modified coal powder.
[0061] Embodiment 3:
[0062] A hydrophobic modified coal powder is prepared by the following steps:
[0063] 1) Dissolve 500 g of Gemini surfactant in 1200 g of water to obtain a surfactant solution, wherein the molecular structure of the Gemini surfactant is 12-2-12 (Br), then add 0.8 g of nano-silica, and ultrasonicate for 20 minutes to obtain a surfactant-nano-silica mixed solution.
[0064] 2) 800 mg of coal powder was added to 600 g of the surfactant-nano-silicon dioxide mixed solution obtained in step (1), and ultrasonication was continued for 30 minutes.
[0065] 3) The mixed solution after ultrasonic adsorption is filtered and then washed with water. The obtained filter cake is placed in an oven at 105° C. and dried for 12 hours to obtain modified coal powder.
[0066] Comparative Example 1:
[0067] 1) Add 800 mg of coal powder into 600 g of water and ultrasonicate for 30 minutes to obtain a mixed solution.
[0068] 2) The mixed solution after ultrasonic treatment is filtered and then washed with water. The filter cake is placed in an oven at 105° C. and dried for 12 hours to obtain modified coal powder.
[0069] Comparative Example 2:
[0070] 1) Disperse 0.8 g of nano-silicon dioxide in 1200 g of water and ultrasonicate for 20 minutes to obtain a nano-silicon dioxide dispersion.
[0071] 2) 800 mg of coal powder was added to 600 g of the nano-silicon dioxide dispersion obtained in step (1), and ultrasonic treatment was continued for 30 minutes.
[0072] 3) The mixed solution after ultrasonic adsorption is filtered and then washed with water. The obtained filter cake is placed in an oven at 105° C. and dried for 12 hours to obtain modified coal powder.
[0073] Comparative Example 3:
[0074] 1) Dissolve 500 g of a Gemini surfactant in 1200 g of water to obtain a surfactant solution. The molecular structure of the Gemini surfactant is 12-2-12 (Br).
[0075] 2) 800 mg of coal powder was added to 600 g of the surfactant solution obtained in step (1), and ultrasonication was continued for 30 minutes.
[0076] 3) The mixed solution after ultrasonic adsorption is filtered and then washed with water. The obtained filter cake is placed in an oven at 105° C. and dried for 12 hours to obtain modified coal powder.
[0077] Effect example:
[0078] The modified coal powder prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was placed in a constant humidity chamber at a humidity of 98% at room temperature for 72 hours, and then the re-absorption moisture rate of the modified coal powder was measured. The specific measurement method was to measure the weight of the coal powder before and after the experiment, calculate the difference and divide it by the weight of the coal powder before the experiment to obtain the re-absorption moisture rate, as shown in the following table.
[0079] sample Reabsorption rate of moisture (%) Example 1 20 Example 2 23 Example 3 17 Comparative Example 1 39 Comparative Example 2 37 Comparative Example 3 26
[0080] It can be seen from the data in the above table that the reabsorption moisture rate of Examples 1 to 3 is significantly lower than that of Comparative Examples 1 to 3. By comparing the data of Example 3 with Comparative Example 1, it can be seen that the reabsorption moisture rate of the hydrophobically modified coal powder of the present application is reduced by 49% compared with the coal powder not treated with Gemini surfactant and nano-silica.
[0081] By comparing the data of Example 3, Comparative Example 1 and Comparative Example 2, it can be seen that the re-absorption moisture rate of the modified coal powder treated only with nano-silicon dioxide is still relatively high, and the re-absorption moisture rate of Comparative Example 2 is not much different from that of Comparative Example 1. This is mainly because the nano-silicon dioxide in Comparative Example 2 has not been modified with a gemini surfactant, resulting in the nano-silicon dioxide still maintaining a negative surface charge, making it difficult to adsorb in the gaps and pore structures of low-rank coal with a negative surface charge.
[0082] By comparing the data of Example 3, Comparative Example 1 and Comparative Example 3, it can be seen that the re-absorption moisture rate of the modified coal powder treated only with the gemini surfactant is lower than that of Comparative Example 1, but is still relatively high. This is mainly because although the surfactant can be partially adsorbed in the gaps and pore structures of the low-rank coal, due to the lack of addition of nano-silicon dioxide, the isolation effect on the gaps and pore structures of the low-rank coal is poor, and a better water inhibition effect cannot be achieved.
[0083] By comparing the data of Example 3, Comparative Example 2 and Comparative Example 3, it can be seen that only treatment with nano-silicon dioxide or only treatment with gemini surfactant cannot give the coal powder a good water inhibition effect. The coal powder must be treated with a mixed solution of gemini surfactant and nano-silicon dioxide to obtain a good water inhibition effect. There is a synergistic effect between gemini surfactant and nano-silicon dioxide.
[0084] The above description of the present disclosure is provided to enable any person of ordinary skill in the art to implement or use the present disclosure. Various modifications to the present disclosure will be apparent to those of ordinary skill in the art, and the general principles corresponding to the present disclosure may be applied to other variations without departing from the scope of protection of the present disclosure. Therefore, the present disclosure is not limited to the examples and designs described herein, but is consistent with the widest range of principles and novel features disclosed herein.
Claims
1. A method for preparing hydrophobically modified coal powder, characterized in that: include: Mixing a surfactant and nano-silicon dioxide in water to obtain a first mixed solution; adding coal powder to the first mixed liquid and mixing to obtain a second mixed liquid; filtering the second mixed liquid, washing, and drying to obtain hydrophobically modified coal powder; The step of adding coal powder to the first mixed liquid and mixing is specifically mixing by ultrasonication for 20 to 60 minutes to destroy the weak interaction between the surfactant and the hydrophobic surface of the coal and retain the strong electrostatic interaction between the surfactant and the hydrophilic surface of the coal.
2. The preparation method according to claim 1, characterized in that: The surfactant is a gemini surfactant.
3. The preparation method according to claim 2, wherein the surfactant is a cationic gemini surfactant, and the surfactant molecular structure is in, m represents the number of carbon atoms in the straight chain alkyl group, and m is 8, 10, 12, 14, 16 or 18; j represents the number of carbon atoms in the bridged branched chain alkyl group, and j is 2, 4 or 6; and X is a bromide ion or a chloride ion.
4. The preparation method according to claim 1, characterized in that: In the step of mixing the surfactant and nano-silicon dioxide in water, the mass ratio of the surfactant, nano-silicon dioxide and water is (0.075-0.60): (0.5-1.0): (1000-1500).
5. The preparation method according to claim 1, characterized in that: The particle size of the nano silicon dioxide is less than 100 nm.
6. The preparation method according to claim 1, characterized in that: In the step of mixing the surfactant and the nano-silicon dioxide in water, the mixing is specifically carried out by ultrasonication for 5 to 40 minutes.
7. The preparation method according to claim 1, characterized in that: The coal powder is dry coal powder, and the particle size of the coal powder is less than 0.5 mm.
8. The preparation method according to claim 1, characterized in that: In the step of adding coal powder to the first mixed liquid for mixing, the mass ratio of the coal powder to the first mixed liquid is (0.50-2.0):(500-1000).
9. A hydrophobic modified coal powder prepared by the preparation method according to any one of claims 1 to 8.